The Effect of Leadership in Organizational Change in Schools - Dandi Gustyan; Ari Anggarani (Jurnal Ilmiah Manajemen Kesatuan, 2024)
In managing organizational transformation, this research examines the function of leadership. In today's world of education, organizational change has emerged as a complex and urgent problem. Effective leadership is essential to managing change successfully. The aim of this research is to examine the role of leadership in the organizational change process, both as a facilitator and as an influencer. Literature review and theoretical analysis were combined with qualitative research methodology in this study. According to the findings, a good leadership style and paying attention to the school culture that has developed is very influential in creating positive change. Teachers, Staff and students can be inspired and motivated by transformational leadership, as they engage in decision making and take ownership of change under participative leadership. Planning, directing, and implementing necessary changes becomes easier with strategic leadership. Practitioners and leaders who want to better manage organizational transformation can greatly benefit from this research. Leaders can adopt important leadership strategies and develop the leadership skills necessary to succeed in facing difficult and dynamic change problems by understanding the function of leadership in the context of organizational change.